Prevalence and Predictors of Abdominal Aorta Calcification in Patients With Psoriasis—A Case Control Study - Ramos, Sofia; Daya, Sheetal; Crowther, Nigel J.; Pillay, Lushen; Tikly, Mohammed; Goolam Mahyoodeen, Nasrin (Frontiers in Medicine, 2022)
BACKGROUND Psoriasis is associated with a high prevalence of cardiovascular disease in Caucasians, but only a few studies from sub-Saharan Africa have investigated the prevalence of cardiovascular disease in patients with psoriasis. Abdominal aortic calcification (AAC) is a strong predictor of future cardiovascular events and all-cause mortality in the general population. We investigated the prevalence and risk factors for AAC in a predominantly non-Caucasian cohort of South African patients with psoriasis. METHODS This was a cross-sectional case-control study of adult psoriasis patients (n=69) and controls (n=80), matched for gender, ethnicity and body mass index, attending tertiary Dermatology and Rheumatology clinics in Johannesburg, South Africa. Demographic, anthropometric, clinical and biochemical data were recorded. All participants underwent non-contrast abdominal CT scans. Images were assessed for AAC at the supra-coeliac aorta, supra-mesenteric aorta and aortic bifurcation using Horos DICOM viewer software. RESULTS Abdominal aortic calcification at any site was more prevalent in the psoriasis than control group (47.8% vs 22.5%, p<0.005). The aortic bifurcation was the commonest site for AAC in both groups, but more prevalent in the psoriasis group (42.0% vs 21.3%, p<0.005). The psoriasis group was also more likely to smoke, have hypertension and type 2 diabetes (56.5% vs 25.0%, p<0.005; 72.0% vs 55.0%, p<0.005; 24.6% vs 3.80%, p<0.0005, respectively). Multivariable logistic regression analysis demonstrated that age, smoking and type 2 diabetes were independently associated with AAC (odds ratio (95% CIs): 1.16 (1.07, 1.20), 4.30 (2.15, 8.61) and 3.45 (1.09, 15.7) respectively), but psoriasis was not. Forward regression analysis demonstrated that smoking attenuated the association of psoriasis with AAC. CONCLUSION In this population, psoriasis is associated with AAC due to the high prevalence of smoking in this patient group. Smoking cessation is essential in psoriatic patients to reduce the risk of cardiovascular events. The clinical utility of AAC detection by CT imaging to risk stratify for hard cardiovascular outcomes needs to be explored.